2016
DOI: 10.1038/nphys3735
|View full text |Cite
|
Sign up to set email alerts
|

Materials research for fusion

Abstract: observation of the degradation of irradiated materials used in the first Q.2 commercial fission reactors. The technological challenges of fusion energy are intimately linked with the availability of suitable materials capable of reliably withstanding the extremely severe operational conditions of fusion reactors. Although fission and fusion materials exhibit common features, fusion materials research is broader. The harder mono-energetic spectrum associated with the deuterium-tritium fusion neutrons (14.1 MeV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
190
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 409 publications
(195 citation statements)
references
References 126 publications
2
190
0
3
Order By: Relevance
“…Future nuclear fusion reactors demand structural materials that can maintain their properties in extreme conditions, such as high temperature, high stress, and intense radiation fluxes123. These increased demands for future technologies cannot be met by incremental improvements to conventional materials.…”
mentioning
confidence: 99%
“…Future nuclear fusion reactors demand structural materials that can maintain their properties in extreme conditions, such as high temperature, high stress, and intense radiation fluxes123. These increased demands for future technologies cannot be met by incremental improvements to conventional materials.…”
mentioning
confidence: 99%
“…Challenges for ceramics in extreme environments arise across broad applications in energy, security, and transportation. Sources for images, from left to right: high‐T c superconductors ( HTSC ) for plasma confinement (reprinted with permission, Nature Publishing Group); armor; ceramic‐matrix composite (reprinted with permission, General Electric Company); reaction zone between environmental barrier coating with calcium‐magnesium‐aluminosilicate; and ultrahigh‐temperature ceramic leading edges (Source: NASA Ames Research Center)…”
Section: Ceramics For Extreme Environmentsmentioning
confidence: 99%
“…More details of these accelerator components and their evolution framed by Fusion materials research can be found in [55, 56]. …”
Section: Figmentioning
confidence: 99%